2019
DOI: 10.1038/s41385-019-0171-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex-associated TSLP-induced immune alterations following early-life RSV infection leads to enhanced allergic disease

Abstract: Many studies have linked severe RSV infection during early-life with an enhanced likelihood of developing childhood asthma, showing a greater susceptibility in boys. Our studies show that early-life RSV infection leads to differential long-term effects based upon the sex of the neonate; leaving male mice prone to exacerbation upon secondary allergen exposure while overall protecting female mice. During initial viral infection, we observed better viral control in the female mice with correlative expression of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 73 publications
7
70
1
Order By: Relevance
“…This result is similar to a prevalence study in Brazil [20]. Nevertheless, some studies in the literature have revealed male as a risk factor to acquire RSV infection, but this observation is currently not well de ned [19,20,21].…”
Section: Discussionsupporting
confidence: 89%
“…This result is similar to a prevalence study in Brazil [20]. Nevertheless, some studies in the literature have revealed male as a risk factor to acquire RSV infection, but this observation is currently not well de ned [19,20,21].…”
Section: Discussionsupporting
confidence: 89%
“…The mice then began CRA sensitization and challenge as previously described. 14,30,31 Briefly, mice were sensitized with 500 protein nitrogen units (PNU) of CRA on days 0, 1, and 2 and challenged with 500 PNU on days 14, 20, 22, and 23. Clinical-grade CRA (as used in skin testing) was used for these experiments.…”
Section: Cockroach Antigen (Cra) Modelmentioning
confidence: 99%
“…Lung sections were stained with hematoxylin and eosin (HE) and periodic acid schiff (PAS). Slides were examined in a blinded fashion by three experienced observers, as previously described [15,16]. For each slide, ten randomly chosen areas were scored.…”
Section: Histological Examination Of Lung Sectionsmentioning
confidence: 99%